Effects of Rosa canina L. Fruit on Glycemia and Lipid Profile in Type 2 Diabetic Patients: A Randomized, Double-Blind, Placebo-Controlled Clinical Trial - Fataneh Hashem Dabaghian; Mehri Abdollahifard; Farideh Khalighi Sigarudi; Maryam Taghavi Shirazi; Asie Shojaee; Zari Sabet; Hasan Fallah Huseini (Institue of Medicinal Plants, ACECR, 2015)
Background: Rosa canina L. (rose hip) has been traditionally used to treat diabetes mellitus in Iran. However, no scientific human study has determined its efficacy in diabetic patients. Objective: This study was conducted to evaluate the efficacy and safety of R. canina fruit aqueous extract in type 2 diabetic patients. Methods: Sixty patients with type 2 diabetes, aged 35 - 60 years with fasting blood glucose levels between 130 to 200 mg/dL and HbA1c between 7 - 9% despite using conventional oral hypoglycemic drugs were divided randomly to two groups. Two groups of 25 and 23 patients completing the trial received 750 mg R. canina fruit extract and 750 mg toast powder as placebo two times a day respectively for three months. Fasting blood glucose (FBG) and glycosylated hemoglobin (HbA1c) as primary outcomes and postprandial blood glucose (PBG), lipid profile and hepatic and renal function tests as secondary outcomes were determined at baseline and at endpoint of treatment. The patients were asked to note down any gastrointestinal or other side effects during the study. Results: The FBG level decreased significantly (P = 0.002) in R. canina group after 3 months compared to the baseline. In addition total cholesterol/HDL-C was significantly (P = 0.02) decreased in the R. canina group compared to the baseline. Other blood parameters were not significantly changed during the study compared with placebo and baseline. No serious side effects were reported in both groups during the study. Conclusion: Rosa canina 3-month administration to type 2 diabetic patients may reduce fasting blood glucose and total cholesterol/HDL-C without any side effect.